2011
DOI: 10.1002/marc.201100223
|View full text |Cite
|
Sign up to set email alerts
|

Well‐defined Biobased Segmented Polyureas Synthesis via a TBD‐catalyzed Isocyanate‐free Route

Abstract: Via an isocyanate-free route, a series of segmented polyureas (PUs) were synthesized from (potentially) renewable resources. To the best of our knowledge, the present work shows for the first time that the organic superbase guanidine 1,5,7-triazabicyclododecene (TBD) which was originally developed as a catalyst for the ring-opening polymerization of lactones, lactides or cyclic carbonates, is also a promising catalyst for the transurethanization between dicarbamates and diamino-terminated poly(propylene glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 26 publications
1
90
0
Order By: Relevance
“…In this respect, the transurethanization approach implying the reaction of a dicarbamate with a diamine can also be considered as a solution to prepare a broad range of polyurea materials. Indeed, Tang et al have recently used this approach to prepare polyurea materials exhibiting thermoplastic elastomer behavior [25].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the transurethanization approach implying the reaction of a dicarbamate with a diamine can also be considered as a solution to prepare a broad range of polyurea materials. Indeed, Tang et al have recently used this approach to prepare polyurea materials exhibiting thermoplastic elastomer behavior [25].…”
Section: Introductionmentioning
confidence: 99%
“…[9,[19][20][21][22][23] Nevertheless, to our knowledge, all the methods reported so far have their drawbacks. Harthcock [20] and his co-workers had to use a cumbersome gel-permeation chromatogram process to isolate individual MDI-butanediol urethane extenders of uniform chain length from random product mixtures to demonstrate their effects.…”
Section: Introductionmentioning
confidence: 89%
“…The phenomenon of polar interactions helps induce their morphological development, which is consistent with Tang's conclusion in previous literature. [19] Moreover, through comparison of melting points and ΔH m values between PU3 (122°C; 16.7 J/ g) and PU4 (132°C; 25.0 J/g), the data clearly showed that longer and more precise extenders form tighter interactions between the PU hard segment chains.…”
Section: Thermal Properties Of Pusmentioning
confidence: 94%
See 1 more Smart Citation
“…[37] Furthermore, many efforts have been made to synthesize directly polyurethanes and polyureas via polycondensation dicarbamates monomers with diols and diamines. [38][39][40][41] Inspired by these studies, we designed and synthesized a novel phosphorus-containing dicarbamates, di(N-carbomethoxyl-aminomethyl)benzyl phosphine oxide from THPS. Five phosphorus-containing polyureas were prepared by trans-ureation polycondensation of di-(N-carbomethoxylaminomethyl)benzyl phosphine oxide with five different diamines catalyzed by 1,5,7-triazabicyclododecene (TBD).…”
Section: Introductionmentioning
confidence: 99%